Hindutv-Mukt Bharat : Dalit-Bahujan, Samajik-Aadhyatmik aani Vaigyanik Krantivareel Chintan. - Ilaiah, Kancha (SAGE Publications, 2017)
Kancha Ilaiah, the author of the best selling book Why I am Not a Hindu, pens a thought-provoking critique of Brahmanism and the caste system in India, while anticipating the death of Hinduism as a direct consequence of, what he says is, its anti-scientific and anti-nationalistic stand. This work challenges Hinduism`s interpretation of history, with a virulent attack on caste politics, and also takes a refreshing look at the necessity of encouraging indigenous scientific thought for the sake of national progress. It establishes Hinduism as a `backward` religion that suppresses the latent scientific and productive potential of the Dalit - Bahujan communities. The author says this oppressive system of spiritual fascism is detrimental to both the future of religion and the nation-state. He thus criticizes the idea of spiritual justice or varnadharma, used to justify the caste system, as rooted in spiritual inequality. On a micro-analytical level, it is based on a thorough study of the productive knowledge systems of the Dalit - Bahujan communities of Andhra Pradesh, and provides a detailed day-to-day analysis of the scientific technological processes and events at work in the life of a member of these communities. On a macro level, it shows how Hinduism fails to negotiate between faith and reason, unlike other major religions of the world. Kancha Ilaiah critiques the intellectual imagination of the dominant communities and inspires the marginalized. In the process of doing so he crafts a work of immense socio-political interest which appeals to academics, and also to all those who are concerned about contemporary India`s polity and social fabric.